Pengaruh Penggunaan Smartphone Terhadap Interaksi Sosial Remaja - Retalia Retalia; Tritjahjo Danny Soesilo; Sapto Irawan (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
This study aims to examine the effect of smartphone use on social interactions of adolescents at Salib Putih Salatiga Orphanage Foundation. This type of research is quantitative research. The sampling technique used was total sampling in order to obtain a sample of 42 teenagers as residents of the Salatiga Orphanage Foundation. The data used is in this study using primary data obtained from the results of a questionnaire or questionnaire. This study uses simple regression analysis techniques and is processed with SPSS version 25 software. The simple linear regression test results show that the intensity of smartphone use has no effect on the social interactions of adolescents at the Salatiga Orphanage Foundation, this is evidenced by a significance level greater than 5% alpha, namely 0.590 > 0.05. Based on the Model Summary data in table 4.8, it can be seen that the value of the R Square is 0.007, which means 0.7%. So it can be concluded that the variable of smartphone use has an effect on social interaction by only 0.7%. and for 99.3% by other factors not described in this study. For this result because it is too small so it can be ignored.